IMPLEMENTATION OF INTEGRATED ONLINE SYSTEM (IOS) IN IMPROVING LEARNING CAPABILITY BASED ON TECHNOLOGY MANAGEMENT - Budianto, Eka Wahyu Hestya; Setiani, Setiani; Retnasih, Nora Ria (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
This research aims to determine: (1) Motivation for implementing IOS in improving technology management-based learning capabilities at the Faculty of Economics; (2) Procedures for implementation; (3) Implications of its application; and (4) Obstacles to its implementation. This research uses a qualitative case study type approach. The research location is the Faculty of Economics at UIN Maulana Malik Ibrahim Malang. Data sources come from primary and secondary data. Data collection techniques include: observations, interviews to seek information and information, and documentation as evidence of research. Meanwhile, data analysis techniques include: data reduction, data presentation, verification and conclusions. Then, data validity checking techniques include: increased persistence and source triangulation. The research results show that: first, there are several motivations for implementing IOS in improving technology management-based learning capabilities at the Faculty of Economics, including: increasing research, innovation, learning quality, resources and accessibility. Second, there are several procedures for implementation, including: curriculum integration, identification of needs, and selection of platform. Third, there are several implications in its implementation, including: increasing accessibility, monitoring, evaluation, integration of the latest technology, student involvement, and time flexibility. Fourth, there are several obstacles in its implementation, including: limited infrastructure, availability of technical support, and internet access.